Program Pengabdian Mahasiswa kepada Keluarga Dhuafa Pak Ido Syams Warga Plumpang Melalui Pengembangan Usaha Seblak - Lakisha Fayza; Mutiara, Mutiara; Hendriani, Putri Faidah; Habibi, Mulkan (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Community empowerment is an effort to increase the dignity of layers of society who are unable to escape the trap of poverty and backwardness. This research aims to analyze the effectiveness of empowering poor people. So far, poverty in Indonesia has been recorded to be still very high, which is largely due to the low level of education of the Indonesian people. Therefore, we formed a program to empower the poor by providing skills training programs as an effort to improve their standard of living. In this empowerment, the method of observation/observations in the field/houses of poor families is used. This method is important to provide valid and precise information. So that the category of poor family can be chosen as the most priority, both in terms of life difficulties, family conditions, and the environment where the poor family lives. The results of this empowerment are being able to provide food such as food needs as well as capital assistance to help the business owned by Mr. Ido Syams' family. Through this community service program, Mr Ido Syams can help the economy. In this way, this community service activity has had a positive impact on families experiencing economic problems Objective: This research aims to analyze the effectiveness of empowering poor people. Method: The method used is Participatory Action Research (PAR) Result: The results of this empowerment are being able to provide food such as food needs as well as capital assistance to help the business owned by Mr. Ido Syams' family. Conclusion: Through this community service program, Mr Ido Syams can help the economy. In this way, this community service activity has had a positive impact on families experiencing economic problems